Chemical composition and in vitro antibacterial activity of essential oils from different species of Juniperus (section Juniperus). (20th July 2020) - Najar, Basma; Pistelli, Luisa; Mancini, Simone; Fratini, Filippo
Abstract: The essential oils (EOs) obtained from leaves belonging to three species of Juniperus (section Juniperus ) collected in different localities of Italy (six samples of J oxycedrus, one sample of J deltoides and three samples of J macrocarpa ), as well as three samples of commercial EOs extracted from Juniperus communis berries, were analysed for their volatile constituents by GC‐MS. The antimicrobial activity of these EOs was tested against both Gram‐negative ( Escherichia coli, Pseudomonas aeruginosa and Salmonella enterica Tiphymurium) and Gram‐positive bacteria ( Enterococcus faecalis, Staphylococcus aureus and Listeria monocytogenes ) ATCC strains. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were determined. The volatile leaf and berry oils were dominated by monoterpene hydrocarbons (from 39.7% of J oxycedrus to 79.0% J macrocarpa ) characterized by high amounts of α‐pinene (an average of 41.3%, 43.0% and 27.6% in J macrocarpa, J oxycedrus and J communis, respectively). On the contrary, limonene was the most abundant compound (20.0%) in J deltoids . The Gram‐positive bacteria evidenced a sensitivity versus EOs extracted from J oxycedrus and J communis, while a moderate susceptibility was showed against J macrocarpa EO J deltoides EO showed the lowest activity between the tested EOs against all the tested strains. Abstract : Volatile analysis of essential oils from leaves of J uniperus oxycedrus, J. deltoides and J. macrocarpa together with J.communis berries. Antimicrobial activity against Gram‐negative ( Escherichia coli, Pseudomonas aeruginosa and Salmonella enterica Tiphymurium) and Gram‐positive bacteria ( Enterococcus faecalis, Staphylococcus aureus and Listeria monocytogenes ) ATCC strains. Gram‐positive bacteria evidenced a sensitivity versus essential oils extracted from J. oxycedrus and J. communis